Land Suitability Assessment Gambir Commodities (Uncaria gambir Roxb.) In Pakpak Bharat Distric Scale 1 : 50.000 - Sebayang, Lukas (Talenta Publisher, 2024)
Gambier (Uncaria gambier Roxb.) is a cultivated plant regeneration in Pakpak Bharat. Gambir extract benefits as well as the pharmaceutical industry and traditional is quite interested so that market opportunities gambier quite open for the domestic market and abroad. Land potential and development opportunities gambir high enough, it is in the use of plantation area of 1,225 ha and optimization of dry land area of 16.049,6 ha (Pakpak Bharat in Figures, 2022). Gambier development in Pakpak Bharat tends to increase, so it is necessary to study the suitability of land to see the direction of the development of the appropriate location. This assessment was conducted by using ALES (Automated Land Evaluation System). SDPLE (Standard Procedure for Land Evaluation) data was imported to ALES program. Land evaluation result was show in spatial form. This form made by imported tabulation data to GIS (Geographical Information System) form. Suitability land maps (scale 1 : 250.000) present based on each commodities by ArcView program. Key words : Land Suitability, gambier, Pakpak Bharat